2010
DOI: 10.1007/s00299-010-0941-6
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis DAL1 and DAL2, two RING finger proteins homologous to Drosophila DIAP1, are involved in regulation of programmed cell death

Abstract: Programmed cell death (PCD) is a precise, genetically controlled cellular process with important roles in plant growth, development, and response to biotic and abiotic stress. However, the genetic mechanisms that control PCD in plants are unclear. Two Arabidopsis genes, DAL1 and DAL2 (for Drosophila DIAP1 like 1 and 2), encoding RING finger proteins with homology to DIAP1 were identified, and a series of experiments were performed to elucidate their roles in the regulation of PCD and disease resistance. Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…Another study reported that SP1 (DAL1) and SPL1 (DAL2) are involved in the regulation of reactive oxygen species (ROS) accumulation and programmed cell death (52). A more recent study showed that SP1 promotes stress tolerance by depleting TOC components, leading to diminished ROS produced in photosynthesis (53).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that SP1 (DAL1) and SPL1 (DAL2) are involved in the regulation of reactive oxygen species (ROS) accumulation and programmed cell death (52). A more recent study showed that SP1 promotes stress tolerance by depleting TOC components, leading to diminished ROS produced in photosynthesis (53).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the turnover of TOC components was affected. Our previous studies have found that the sterile anther in 7365A displays delayed tapetal programmed cell death (PCD) Zhou et al, 2011;Song et al, 2016), and another study reported that SP1 is involved in the regulation of PCD (Basnayake et al, 2011). So, SP1 mediating UPS may be affected in 7365A.…”
Section: Researchmentioning
confidence: 99%
“…For example, In A. thaliana, BRH1 is involved in brassinosteroid-responsive19, RIE1 in seed development20, ATL2/ATL9 in defense response2122, XERICO in drought tolerance23, KEG in growth and development24, PEX2/PEX10/PEX12 in peroxisome formation2526, NLA in adaptability to nitrogen limitation27, SHA1 in shoot apical meristem maintenance28, SDIR1 in stress-responsive abscisic acid signaling29, DRIP1 / DRIP2 is in drought response30 , RHA2a/RHA2b in ABA-mediated stress signaling3132, CNI1 in the carbon/nitrogen response for growth phase transition33, SIS3 in sugar response34, XBAT32 in lateral root production by regulating the ethylene biosynthesis35, AtAIRP1 in ABA-dependent response to drought stress36, DAL1/DAL2 in regulation of programmed cell death37, DAF in anther dehiscence38, AtAIRP3 in high-salt and drought stress responses39, RSL1 in seed longevity40, AtRING1A in flowering41, COP1 in photomorphogenesis42, NERF in drought resistance43, STRF1 in salt-stress response44; in B. rapa, BrRZFP1 is involved in cold, salt and dehydration stress45; in B. napus, Bnclg1A-1D is involved in cleistogamy trait formation46.…”
mentioning
confidence: 99%